Molecular biogeography of planktonic and benthic diatoms in the Yangtze River - Wang, Jiawen; Liu, Qingxiang; Zhao, Xianfu; Borthwick, Alistair GL; Yuxin Liu; Qian Chen; Ni, Jinren (MicrobiomeMicrobiome, 2019)
Background: Diatoms are of great significance to primary productivity in oceans, yet little is known about their biogeographic distribution in oligotrophic rivers. Results: With the help of metabarcoding analysis of 279 samples from the Yangtze River, we provided the first integral biogeographic pattern of planktonic and benthic diatoms over a 6030 km continuum along the world's third largest river. Our study revealed spatial dissimilarity of diatoms under varying landforms, including plateau, mountain, foothill, basin, foothill-mountain, and plain regions, from the river source to the estuary. Environmental drivers of diatom communities were interpreted in terms of photosynthetically active radiation, temperature, channel slope and nutrients, and human interference. Typical benthic diatoms, such as Pinnularia, Paralia, and Aulacoseira, experienced considerable reduction in relative abundance downstream of the Three Gorges Dam and the Xiluodu Dam, two of the world's largest dams. Conclusions: Our study revealed that benthic diatoms are of particular significance in characterizing motile guild in riverine environments, which provides insights into diatom biogeography and biogeochemical cycles in large river ecosystems.